Electronic Publishing Programs: Issues to Consider - Elizabeth W. Brown; Andrea L. Duda (Issues in Science and Technology Librarianship, 1996)
At first glance, the proliferation of Web journal publishing, particularly from the commercial sector recently, may seem like manna from heaven -- librarians can now offer users searchable full-text of important scientific journals, as well as enhancements found only in the electronic versions. When it comes to electronic publications, however, librarians must consider a host of details.